The Role of the EZH2 and H3K27me3 Expression as a Predictor of Clinical Outcomes in Salivary Duct Carcinoma Patients: A Large-Series Study With Emphasis on the Relevance to the Combined Androgen Blockade and HER2-Targeted Therapy - Saigusa, Natsuki; Hirai, Hideaki; Tada, Yuichiro; Kawakita, Daisuke; Nakaguro, Masato; Tsukahara, Kiyoaki; Kano, Satoshi; Ozawa, Hiroyuki; Kondo, Takahito; Okami, Kenji; Togashi, Takafumi; Sato, Yukiko; et al. (Frontiers in Oncology, 2022)
Objective: Salivary duct carcinoma (SDC) is a highly aggressive and uncommon tumor arising not only de novo but also in pleomorphic adenoma. Androgen receptor (AR)- and HER2-targeted therapy have recently been introduced for SDC as promising treatment options; however, no predictive biomarkers have yet been established. EZH2 and H3K27me3 are closely linked to the development and progression of various cancers, and EZH2 is also expected to be a desirable therapeutic target. We therefore explored the clinicopathological and prognostic implications of EZH2 and H3K27me3 in a large cohort of SDC patients, focusing on their impact on the therapeutic efficacy of AR- or HER2-targeted therapy. Materials and Methods: The EZH2 and H3K27me3 immunohistochemical expression and EZH2 Y646 gain-of-function mutation status were examined in 226 SDCs, and the relationship with the clinicopathological factors as well as clinical outcomes were evaluated within the three groups depending on the treatment: AR-targeted (combined androgen blockade with leuprorelin acetate and bicalutamide; 89 cases), HER2-targeted (trastuzumab and docetaxel; 42 cases), and conventional therapy (112 cases). Results: EZH2 and H3K27me3 were variably immunoreactive in most SDCs. A positive correlation was found between the expression of EZH2 and H3K27me3. The EZH2 expression in the SDC component was significantly higher than that in the pre-existing pleomorphic adenoma component. EZH2 Y646 was not identified in any cases. EZH2-high cases more frequently had an advanced clinical stage and aggressive histological features than EZH2-low cases. An EZH2-high status in patients treated with AR-targeted therapy was associated with a significantly shorter progression-free and overall survival as well as a lower objective response rate and clinical benefit rate. In addition, a H3K27me3-high status in patients treated with AR-targeted therapy was related to a shorter overall survival. Conversely, there was no association between the EZH2 and H3K27me3 expression and the clinical outcomes in the conventional or HER2-targeted therapy groups. Conclusions: A high expression of EZH2 and H3K27me3 in SDC might be a predictor of a poor efficacy of AR-targeted therapy. Our data provide new insights into the role of EZH2 and H3K27me3 in therapeutic strategies for SDC.